Cost-effectiveness Study in Type 2 Diabetes Mellitus in Asia: A Review - Wiracana, I Made; Priyatni, Nunung; Virginia, Dita Maria (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Background: Type 2 Diabetes Mellitus (DM) requires intensive treatment to prevent progression and complications. One of the intensive treatments is insulin therapy. The increase in insulin price and variation in insulin therapy results in differences in treatment costs. In Asia, commonly used types of insulin therapy are NPH insulin and glargine insulin. It is urgent to define the most cost-effective insulin therapy among type 2 DM patients because of the economic burden.Objectives: This study aims to assess the cost-effectiveness of these insulin types. We did a narrative review using literature discussing the cost-effectiveness of insulin for type 2 DM patients.Methods: This study employs a narrative review approach using the PRISMA-P 2015 structured approach to examine studies. This article's methodological quality was evaluated using the Drummond checklist. The terms